Data Collection Methods in Didactics of Physics in the International Environment - Žák, Vojtěch (Scientia in educatione, 2016)
The strategic goal of the research, which also includes this systematic review, is to reï¬ect the development and current situation in the ﬁeld of physics education research (hereafter referred to as PER). The purpose of the review is to present an outline of data collection methods and to foster discussion about research methods used in this ﬁeld. Qualitative approach was used to deal with the research problem, complemented by the content analysis of research studies as a data collection method. The SCOPUS database was chosen as a source of the analysed texts, yet the analysis was limited only to relevant journal articles, 146 in total, published in English between 2010 and 2014. The data collection methods used in PER include questionnaires, interviews, and achievement tests (which are predominantly conceptual). Furthermore, there are analyses of various documents, observations, or other methods. A beneﬁt for further research in the ﬁeld of PER, both on the local or international level, may be the fact that standardised research methods are used in the international environment, particularly conceptual tests and questionnaires. This study abstracts away, to a certain extent, from the realm of physics. This is why the presented ﬁndings may be beneﬁcial also for other researchers in the ﬁeld of science education.